Ethylene Signaling Mediates a Maize Defense Response to Insect Herbivory - Antoine L. Harfouche; Renuka Shivaji; Russell Stocker; Paul W. Williams; Dawn S. Luthe (Molecular Plant-Microbe Interactions, 2006)
The signaling pathways that enable plants to mount defenses against insect herbivores are known to be complex. It was previously demonstrated that the insect-resistant maize (Zea mays L.) genotype Mp708 accumulates a unique defense cysteine proteinase, Mir1-CP, in response to caterpillar feeding. In this study, the role of ethylene in insect defense in Mp708 and an insect-susceptible line Tx601 was explored. Ethylene synthesis was blocked with either cobalt chloride or aminoethoxyvinylglycine. Alternatively, ethylene perception was inhibited with 1-methylcyclopropene. Blocking ethylene synthesis and perception resulted in Mp708 plants that were more susceptible to caterpillar feeding. In addition, fall armyworm (Spodoptera frugiperda) larvae that fed on inhibitor-treated Mp708 plants had signifycantly higher growth rates than those reared on untreated plants. In contrast, these responses were not significantly altered in Tx601. The ethylene synthesis and perception inhibitors also reduced the accumulation of Mir1-CP and its transcript mir1 in response to herbivory. These results indicate that ethylene is a component of the signal transduction pathway leading to defense against insect herbivory in the resistant genotype Mp708.